« En face avec une brutalité candide » : genèse de la première rencontre entre Charles et Emma dans Madame Bovary - Biagio Magaudda (Flaubert: Revue Critique et Génétique)
Flaubert's manuscript drafts of Madame Bovary concerning the first sight scene between Charles and Emma proved very valuable and illuminating because it allowed us to examine how this meeting arose in Flaubert's imagination and to what extent the writer operated through allusions, the symbolic representation of objects and the unsaid.